Cross-Functional Integration and the Success of Servitization Production of Manufacturers - Examination of the Necessary Conditions - Mirosław MATUSEK (Communications of International Proceedings, 2020)
The aim of the article was to examine the level of necessity of the condition of inter-functional integration in the organization to achieve different levels of revenues from the sale of services of production enterprises depending on the type of service orientation of the product offer (i.e. product support services (SSP) and customer support services (SSC). Servicing is now becoming an important factor contributing to the competitiveness of producers. This phenomenon, understood as the adoption of a service-oriented business strategy, in line with the theory of organizational fit, requires changes, e.g., in the organizational structure. Producers may separate an autonomous service unit or strive to integrate a service organization with a product. There are arguments for one or the other in the results of empirical research and in theory. Unfortunately, the results currently achieved show a contradiction. On the basis of a survey conducted on a sample of 186 manufacturers, the necessary conditions were tested using one of the non-parametric methods, i.e., Necessary Condition Analysis (NCA). The study showed that cross-functional cooperation determines the achievement of different levels of revenues from the provision of product and service solutions. This condition severely limits the revenues generated when the manufacturer provides the SSC category offer.
Keywords: Servitization; Service Orientation; Industry 4.0; Organizational Ties; Necessary Condition Analysis (NCA).